Antarctic Sea Ice Area in CMIP6. Issue 9 (2nd May 2020) - Roach, Lettie A.; Dörr, Jakob; Holmes, Caroline R.; Massonnet, François; Blockley, Edward W.; Notz, Dirk; Rackow, Thomas; Raphael, Marilyn N.; O'Farrell, Siobhan P.; Bailey, David A.; Bitz, Cecilia M.
Abstract: Fully coupled climate models have long shown a wide range of Antarctic sea ice states and evolution over the satellite era. Here, we present a high‐level evaluation of Antarctic sea ice in 40 models from the most recent phase of the Coupled Model Intercomparison Project (CMIP6). Many models capture key characteristics of the mean seasonal cycle of sea ice area (SIA), but some simulate implausible historical mean states compared to satellite observations, leading to large intermodel spread. Summer SIA is consistently biased low across the ensemble. Compared to the previous model generation (CMIP5), the intermodel spread in winter and summer SIA has reduced, and the regional distribution of sea ice concentration has improved. Over 1979–2018, many models simulate strong negative trends in SIA concurrently with stronger‐than‐observed trends in global mean surface temperature (GMST). By the end of the 21st century, models project clear differences in sea ice between forcing scenarios. Plain Language Summary: Coupled climate models are complex computer programs that simulate the interaction of the atmosphere, ocean, land surface, and cryosphere. An important feature of the Southern Ocean is its sea ice cover, which typically expands in winter to cover an area comparable to that of Russia. Climate models have shown very different amounts of Antarctic sea ice coverage and very different trajectories of sea ice change in response to expected greenhouse gas emissions. This year, new coupled climate models released under the Coupled Model Intercomparison Project (CMIP6) will form the basis of the next IPCC assessment report. Here, we compare output from those models to satellite observations of the areal coverage of sea ice. As a whole, the models successfully capture some elements of the observed seasonal cycle of sea ice but underestimate the summer minimum sea ice area. Compared to results from the previous model generation (CMIP5), the range across models has reduced, and the location of sea ice agrees better with observations. Models project sea ice loss over the 21st century in all scenarios, but confidence in the rate of loss is limited, as most models show stronger global warming trends than observed over the recent historical period. Key Points: CMIP6‐mean Antarctic sea ice area is close to observations, but intermodel spread remains substantial We find modest improvements in the simulation of sea ice area and concentration compared to CMIP5 Most CMIP6 models simulate sea ice losses and stronger‐than‐observed GMST trends over 1979–2018